THE PHENOMENA OF THE DELAYING AGE OF FIRST MARRIAGE AND ITS IMPLICATIONS FOR POPULATION GROWTH IN NORTH SUMATRA - Handayani, Siti Alifah; Hidayat, Nasrullah; Wijaya, Meisha Fatma; Simanjuntak, Tessalonika Federova (Universitas Negeri Medan, 2024)
This study investigates the postponement of the age of first marriage and its implications for population growth and demographic structure in North Sumatra Province. The research utilizes qualitative methods to obtain clear and in-depth information. It employs secondary data collected and published by other sources to analyze trends in delaying the age of first marriage and its impact on population growth. Findings indicate a significant trend of delaying first marriage, especially among youth, with an observed increase in 2023. Factors such as access to education, changes in social values, and economic conditions influence the decision to postpone marriage. This postponement affects fertility and population growth, potentially reducing the birth rate. However, despite the decline in birth rates, population growth continues due to factors such as migration. The study emphasizes the importance of considering various factors, including migration, in demographic analysis and development planning to accommodate the complex dynamics of the population and meet the needs of the community comprehensively.